Why Do Your Customers switch to Other E-commerce Platforms? - Aziz, Noviawan Abdul; Taufik, Nuryanti; Herdiyanti, Herdiyanti (Sharia Business Management UIN Raden Intan Lampung, 2024)
The phenomenon of e-commerce use is experiencing rapid growth among the public, causing high competition between e-commerce companies in Indonesia. Shopee is one of the e-commerce companies that is experiencing this competition, experiencing a decline in the number of users and suffering losses of up to 115% during 2021-2022 due to the presence of many new e-commerce platforms. This research aims to examine the influence of user interface and security on customer loyalty with user experience as a mediating variable on the Shopee e-commerce platform in Indonesia. This research uses a survey method with a quantitative approach. The analytical tool used is Structural Equation Modeling (SEM) with AMOS version 24 software. Research data was obtained from respondents using a questionnaire that was distributed to 215 Shopee customers in Indonesia. The results show that user interface and security influence user experience, which in turn influences customer loyalty. User experience also acts as a mediator in the relationship between user interface and security on customer loyalty. This research provides theoretical and practical contributions to the development of e-commerce service management strategies that consumers need and want.